The Extension of The Corpus of Central American Colonial Literature: Theoretical Reflections - Sánchez Mora, Alexánder (2019)
This article proposes expanding the corpus of Central American colonial literature through an openning that alllows including texts that had been defined exclusevely as historical documents from a traditional generic perspective. Taking into account some proposals of the historian Hayden White, the aesthetics of the German reception of Hans R. Jauss, along with cognitive semantics, it is intended to show how the textual tradition of Baroque festivals, ranging from the mid-17th to the early 19th centuries, constitutes an essential part of the literary discursive formation of the Central American Baroque.